2006
DOI: 10.1007/s11430-006-1079-9
|View full text |Cite
|
Sign up to set email alerts
|

Climatic and environmental changes over the last millennium recorded in the Malan ice core from the northern Tibetan Plateau

Abstract: In this paper, climatic and environmental changes were reconstructed since 1129A.D.based on the Malan ice core from Hol Xil, the northern Tibetan Plateau. The record of δ 18 O in the Malan ice core indicated that the warm-season air temperature variations displayed a general increase trend, the 20th-century warming was within the range of natural climate variability, and the warmest century was the 17th century while the warmest decade was the 1610s, over the entire study period. The "Medieval Warm Epoch" and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 42 publications
2
33
0
1
Order By: Relevance
“…Among them, data from NE and SE are extended to 2000 based on records of warm/cold periods in historical documents (Hao et al, 2011). In TP and NW, some of the original temperature proxies have been updated (in TP: Thompson et al, 2000Thompson et al, , 2003Thompson et al, , 2006Shen et al, 2001;Liu et al, 2006;Wang et al, 2006;Zhu et al, 2008;in NW: Liu et al, 2005;Zhang et al, 2011), and we were able to re-evaluate the records of temperature change in these two regions using the method of Ge et al (2010). The decadal temperature time series extends from 1 to 2000 in CE, TP and NE; from 851 to 2000 in NW; and from 1471 to 2000 in SE.…”
Section: Q Ge Et Al: Temperature Changes Over the Past 2000 Yr In Cmentioning
confidence: 99%
“…Among them, data from NE and SE are extended to 2000 based on records of warm/cold periods in historical documents (Hao et al, 2011). In TP and NW, some of the original temperature proxies have been updated (in TP: Thompson et al, 2000Thompson et al, , 2003Thompson et al, , 2006Shen et al, 2001;Liu et al, 2006;Wang et al, 2006;Zhu et al, 2008;in NW: Liu et al, 2005;Zhang et al, 2011), and we were able to re-evaluate the records of temperature change in these two regions using the method of Ge et al (2010). The decadal temperature time series extends from 1 to 2000 in CE, TP and NE; from 851 to 2000 in NW; and from 1471 to 2000 in SE.…”
Section: Q Ge Et Al: Temperature Changes Over the Past 2000 Yr In Cmentioning
confidence: 99%
“…Rsearches have proved that the δ 18 O components in the ice cores were reliable substitute index of temperature (e.g. Yao and Thompson 1992;Thompson et al, 1993;Yao et al, 1997;Wang N et al, 2006). However, the isotope information interpretation was largely depended on the knowledge of variation characteristics of stable isotope information contained in the modern precipitation (Yu et al, 2006).…”
Section: δ 18 O Thermometermentioning
confidence: 99%
“…ratio of dust layer thickness to ice thickness (i.e. the dust ratio) could be used as a proxy for dust event frequency in the Malan ice core, and found that the variations in the dust ratio were similar to the variations in dust events occurring in south Xingjiang over the past decades [26] . Figure 2(a) illustrates the variations in the dust ratio over the past century.…”
Section: Dust Proxies and Their Data Seriesmentioning
confidence: 88%